Correlation between Acute Stroke and Concentration of Creatine Kinase Myocardial Band, Troponin T, Hemoglobin, and Electroyltes (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Currently, there were only a few studies regarding the correlation between concentration of creatine kinase-myocardial band (CKMB), troponin T, hemoglobin, and electrolytes and acute stroke. This study aimed to understand the difference of mean concentration of CKMB, troponin T, hemoglobin, and electrolytes and their relationship with acute stroke. This was a cross sectional study using samples of 30 subjects who were selected with consecutive non random sampling. The subjects were acquired from acute stroke patients who were proven clinically and using computed tomography (CT) scan at Haji Adam Malik General Hospital. Demographic data were analyzed using descriptive statistic. The result showed that there were no difference in demographical characteristics between the subjects. In conclusion, there were no differences in mean of CKMB, troponin T, hemoglobin, and electrolytes in acute stroke. No correlation was found between acute stroke and concentration of CKMB, troponin T, hemoglobin, and electrolytes.